THE IMPACT OF THE COVID-19 PANDEMIC ON THE POSITION OF LABOR MIGRANTS FROM CENTRAL ASIA IN RUSSIA - RYAZANTSEV, Sergey; VAZIROV, Zafar; KHRAMOVA, Marina; SMIRNOV, Alexey (CENTRAL ASIA AND THE CAUCASUS, 2024)
The article examines the impact of the COVID-19 pandemic on the position of Central Asian labor migrants in Russia. The article notes the signi labor migration in the formation of Russia’s gross domestic product and budget. The ethnic specialization of Central Asian labor migrants in the Russian economy is described: migrants from Uzbekistan and Tajikistan work in construction and agriculture, those from Kyrgyzstan—in trade, the service sphere and public catering. The economic downturn during the COVID-19 pandemic reduced the employment rate of labor migrants from Central Asian countries in the Russian economy signi merous workers from Tajikistan and Uzbekistan engaged in construction, maintenance and transport lost their jobs. A sociological survey of labor migrants revealed that the key problems of Central Asian labor migrants during the pandemic were the loss of work and income, the inability to pay for housing and food, and increased pressure from the security forces. Considering the signi scale of the decline in production and the growth of unemployment among labor migrants in Russia, the volume of money transfers to Central Asian countries is expected to decrease in the coming months. The highest rates of decline are expected in Tajikistan and Uzbekistan, to a lesser extent in Kyrgyzstan. The coordination of Russia’s actions with the donor countries of Central Asia in the sphere of humanitarian aid, transportation of migrants to their homeland, and reduction of pressure on migration communities should be a key area at the international level.